2015
DOI: 10.1186/s12883-015-0394-1
|View full text |Cite
|
Sign up to set email alerts
|

Latitude, sun exposure and vitamin D supplementation: associations with quality of life and disease outcomes in a large international cohort of people with multiple sclerosis

Abstract: BackgroundA growing evidence base implicates vitamin D, sun exposure and latitude in the aetiology of multiple sclerosis (MS), however there are less data on the associations of these variables with disease outcomes.MethodsWe undertook a cross-sectional survey of over 2000 people with MS recruited through internet platforms, seeking self-reported data on geographical location, intentional sun exposure for health, and supplementation with vitamin D, among other lifestyle variables. We also requested data on hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 26 publications
(21 reference statements)
4
33
0
2
Order By: Relevance
“…In keeping with recent research showing higher relapse rate [21, 35] and disability [35] with increasing latitude, our data showed 1-2 points lower PHC for every 10 degrees in latitude further from the equator, an association that, while potentially modifiable, may not be of clinically relevant magnitude. Those with normal BMI compared with overweight or obesity had a 2-3 point better PHC.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In keeping with recent research showing higher relapse rate [21, 35] and disability [35] with increasing latitude, our data showed 1-2 points lower PHC for every 10 degrees in latitude further from the equator, an association that, while potentially modifiable, may not be of clinically relevant magnitude. Those with normal BMI compared with overweight or obesity had a 2-3 point better PHC.…”
Section: Resultssupporting
confidence: 91%
“…Our previous research has separately examined associations of a number of individual lifestyle risk factors with QOL in a large international sample of people with MS, allowing detailed analysis of the relationship between QOL and diet [19] including specific dietary components [20], latitude and vitamin D supplementation [21], physical activity [22], alcohol consumption and cigarette smoking [23], and body mass index (BMI) and number of comorbidities [24], as well as DMD use [25]. These studies did not however allow comparison of the relative magnitude of these associations while mutually adjusting for other modifiable lifestyle factors, medication use and potentially related socio-demographic factors.…”
Section: Introductionmentioning
confidence: 99%
“…The authors evaluated the clinical effectiveness of vitamin D supplementation in four systematic reviews (2730), eight randomized controlled trials (24, 3137), and three non-randomized studies (25, 38, 39). The authors of the CADTH Rapid Report concluded that “the outcomes of vitamin D supplementation for MS were heterogeneous, conflicting and inconsistent, with no effect on disability scores and relapse rates.…”
Section: Why Establish Phocis While a Trial Of Oral Vitamin D Supplemmentioning
confidence: 99%
“…Quality of life could be regarded an integrative measure of self‐perceived health. This should be highly relevant in the context of the possible pleiotropic effects of vitamin D, where quality of life could be considered a composite end‐point integrating various health effects of vitamin D. Observational studies have reported positive associations between serum 25(OH)D levels and quality of life . The results from intervention studies are, however, conflicting …”
Section: Introductionmentioning
confidence: 99%